GIDDENS, A. MUNDO EM DESCONTROLE. TRAD. M. L. S. DE A. BORGES. RIO DE JANEIRO: RECORD, 2000, 108 PÁGS. - Pacheco, Marta C. de Noronha (Cadernos de Linguagem e Sociedade, 2010)
GIDDENS, A. MUNDO EM DESCONTROLE. TRAD. M. L. S. DE A. BORGES. RIO DE JANEIRO: RECORD, 2000, 108 PÁGS.